Beyond heroism: a qualitative study on the lived experiences of nurses caring for patients with COVID-19 in Pakistan - Mahreen Afzal; Muhammad Abo ul Hassan Rashid; Florian Fischer (BMC, 2023)
Abstract Background Healthcare professionals around the globe suffered severely during the COVID-19 pandemic. The present study aims to explore the lived experiences of nurses caring for COVID-19 patients in Pakistan. Methods The study is a qualitative exploration of the lived experiences caring for patients with COVID-19 in Pakistan. This research was conducted in two government hospitals there. Face-to-face in-depth interviews were conducted amongst 30 nurses who had been selected using purposive sampling technique. Thematic analysis was applied to extract the themes from respondents' answers. Results By using thematic analysis, social response, impacts on physical and mental health, and experience of handling COVID-19 patients were extracted as major themes. Conclusions The findings of this research are of immense importance in showing the impact of COVID-19 on mental and physical health, along with the social and personal consequences for nurses providing care to COVID-19 patients.